In-cylinder expansion of ring crevice hydrocarbons in SI engines - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
This paper presents the results of a theoretical study devoted to diffusion and removal of ring crevice HC's, compressed into the crevices during compression and partly combustion stroke. The model consists of three major submodels. First is prediction of time-varying composition of combustion gases, second is modelling the release of the ring crevice HC's during late expansion and exhaust stroke and the last one is a simple phenomenological approach for calculation of temperature variation with crank angle. Valve overlap period is excluded in the solution to be capable of assuming centrally located single valve for sake of adapting a 2D solution scheme. Flow field and HC concentrations are determined by solution of Navier-Stokes equations and equation of conservation of chemical species respectively. But instead of energy equation, above mentioned phenomenological submodel is introduced for calculation of temperature, despite the fact that it disturbs the nature of solution procedure of Navier-Stokes equations. Oil film HC's and postflame oxidation are excluded, as for the last, solution procedure enhances the period after which in cylinder oxidation ceases. Result are presented at the extend limited counterparts allow, due to the lack of common parameters adapted in different studies amongst plenty of them. (C) 2003 Elsevier Science Ltd.